Introductory real analysis - Dangello, Frank; Seyfried, Michael (Boston : Houghton Mifflin, 2000)
This book is about: Proofs, Sets, and functions; The structure of R; Sequemces; Continuity; Differentiation; ...
Keywords: Mathematical analysis; Mathematical analysis